Fossil avian eggshell preserves ancient DNA - Oskam, C.; Haile, James; McLay, E.; Rigby, P.; Allentoft, M.; Olsen, M.; Bengtsson, C.; Miller, Gifford; Schwenninger, J.; Jacomb, C.; Walter, R.; Baynes, A.; et al. (The Royal Society Publishing, 2010)
Owing to exceptional biomolecule preservation, fossil avian eggshell has been used extensively in geochronologyand palaeodietary studies. Here, we show, to our knowledge, for the first time that fossil eggshell is apreviously unrecognized source of ancientDNA (aDNA).We describe the successful isolation and amplificationofDNAfrom fossil eggshell up to 19 ka old. aDNAwas successfully characterized fromeggshell obtainedfrom New Zealand (extinct moa and ducks), Madagascar (extinct elephant birds) and Australia (emu andowl). Our data demonstrate excellent preservation of the nucleic acids, evidenced by retrieval of both mitochondrialand nuclear DNA from many of the samples. Using confocal microscopy and quantitative PCR,this study critically evaluates approaches to maximizeDNA recovery from powdered eggshell. Our quantitativePCR experiments also demonstrate that moa eggshell has approximately 125 times lower bacterial loadthan bone, making it a highly suitable substrate for high-throughput sequencing approaches. Importantly,the preservation ofDNAin Pleistocene eggshell fromAustralia andHolocene deposits fromMadagascar indicatesthat eggshell is an excellent substrate for the long-term preservation of DNA in warmer climates. Thesuccessful recovery of DNA from this substrate has implications in a number of scientific disciplines; mostnotably archaeology and palaeontology, where genotypes and/or DNA-based species identifications canadd significantly to our understanding of diets, environments, past biodiversity and evolutionary processes.